2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7592027
|View full text |Cite
|
Sign up to set email alerts
|

Feature domain-specific movement intention detection for stroke rehabilitation with brain-computer interfaces

Abstract: Brain-computer interface (BCI) driven electrical stimulation has been proposed for neuromodulation for stroke rehabilitation by pairing intentions to move with somatosensory feedback from electrical stimulation. Movement intentions have been detected in several studies using different techniques, with temporal and spectral features being the most common. A few studies have compared temporal and spectral features, but conflicting results have been reported. In this study, the aim was to investigate if complexit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Moreover, no interventions so far have tested BMI platforms decoding pre-movement BP and ERD patterns online in patients with brain damage due to a stroke. While BP detections online in healthy subjects doing ankle dorsiflexions have demonstrated to be reliable for BMI approaches, BPs in upper-limb movements (Hadsund et al, 2016 ; Martínez-Expósito et al, 2017 ), and specially in stroke patients (Daly et al, 2006 ) present particularities that make them less reliable for BMI applications, which may limit their usability in BMIs. Recently, it was demonstrated that an appropriate combination of BP- and ERD-based classifiers could lead to reliable and low-latency estimation of stroke patients' upper-limb motor intentions (Ibáñez et al, 2014a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, no interventions so far have tested BMI platforms decoding pre-movement BP and ERD patterns online in patients with brain damage due to a stroke. While BP detections online in healthy subjects doing ankle dorsiflexions have demonstrated to be reliable for BMI approaches, BPs in upper-limb movements (Hadsund et al, 2016 ; Martínez-Expósito et al, 2017 ), and specially in stroke patients (Daly et al, 2006 ) present particularities that make them less reliable for BMI applications, which may limit their usability in BMIs. Recently, it was demonstrated that an appropriate combination of BP- and ERD-based classifiers could lead to reliable and low-latency estimation of stroke patients' upper-limb motor intentions (Ibáñez et al, 2014a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the spectral features, raw EEG signals were band-pass filtered in theta (4-8 Hz), alpha (8)(9)(10)(11)(12)(13), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and gamma (30-80) bands using a zero phase second order Butterworth filter, and then squared. The filtered signals were then segmented into movement and rest epochs, and the mean was calculated over the same sliding windows as for the temporal features to estimate the average power.…”
Section: Feature Extraction and Selectionmentioning
confidence: 99%
“…This technique outperformed movement detection using template matching with raw EEG samples [21]. Another approach to constructing temporal features is to divide the signal segment into windows, with or without overlap, and then compute average parameters, such as the mean, slope and variability [23][24][25]. Temporal parameters extracted from an MRCP can be supplemented with spectral features capturing the change in power within relevant frequency bands [18,26].…”
Section: Introductionmentioning
confidence: 99%